Development of Educational Activity at the University of Maribor - Sotlar, Andrej; Frumen, Sebastijan (50 let Univerze v Mariboru: Pol stoletja znanja in raziskovanja, 2026)
The educational activity currently carried out by the University of Maribor has its roots in higher vocational and higher education, which began at the institutions that would later become its constituent members, approximately a decade and a half prior to the University’s formal establishment. The development of study programmes was initially guided by the needs of the local community, gradually expanding to address broader economic and societal demands. Following the founding of the University, the range of study programmes and fields of study expanded rapidly, particularly through the establishment or integration of new faculties. At present, the University of Maribor comprises seventeen members, collectively offering 178 study programmes across all levels of higher education in the fields of engineering, natural sciences, agriculture, medicine, social sciences, and the humanities. A diverse and comprehensive selection of study programmes, their continual adaptation to societal needs, an interdisciplinary orientation, a strong commitment to internationalisation, and a consistent rate of student enrolment are key features of its academic engagement. These attributes position the University of Maribor as a significant national higher education institution, which has long since transcended its local and regional origins and now confidently asserts its presence within the global academic sphere.